Income and Subjective Well-Being: A Case Study - Boo Mei Chin; Yen Siew Hwa; Lim Hock Eam (Kajian Malaysia, 2020)
This article examines to what extent income could influence subjective well-being based on a case study involving 249 working adult students from the School of Distance Education at Universiti Sains Malaysia (USM). Subjective well-being is represented by the respondent’s level of happiness and life satisfaction. The outcomes show happiness and life satisfaction are affected by household income, relative income, expected income and health. Household income seems to matter more in influencing both happiness and life satisfaction as compared to relative income. Respondents are less happy and less satisfied when the gap between their actual and expected income became larger. This study shows that better health status increases one’s happiness and life satisfaction. Being divorced, separated or widowed compared to being single shows an adverse impact on their happiness but has no significant influence on their life satisfaction. Age and life satisfaction displayed an inverted U-shaped relationship indicating that life satisfaction among the respondents reaches its peak at age 44 and starts to decline after that. The Malays seemed to be more satisfied with their lives as compared with the other ethnic groups.